252 Physicians' Perceptions to Electronic Alerts for Delirium and Dementia Screening - Qualitative Analysis of Bypass Reasons in an Electronic Patient Record. (16th September 2019) - Rice, Darragh; Chapman, Lucy; Corbett, Mel; Courtney, Grainne; Lawlor, Brian
Abstract: Background: Delirium and dementia are common cognitive disorders within an inpatient hospital population (Mukadam & Sampson 2010) Efforts were made to improve detection by embedding the 4As Test (4AT) cognitive screening tool within the hospital electronic patient record (EPR). Non consultant hospital doctors (NCHDs) and consultants were prompted to complete the electronic 4AT on all inpatients aged 65 years and over at 24 hours into admission. Doctors could opt to bypass completion of the screening assessment but a reason for bypassing was required. Methods: Reasons for bypassing the 4AT electronic alert were analysed using mixed methods during a seven week time period between June 28 th and August 16 th 2018. Free text entries were grouped into 15 qualitative categories. Quantitative methods using descriptive statistics were subsequently applied to qualitative categorisation. Results: During seven weeks of analysis, hospital doctors bypassed electronic 4AT screening on 2473 occasions equating to a mean of 50.5 bypasses per day. Overall 40% of free text reasons documented were unintelligible. Examples of unintelligible bypass reasons documented in the EPR included "2321" and "dghj". Amongst the qualitative categories analysed, the most common reasons for bypass observed were "Accessing EPR Remotely from Patient" (33%), "Specific Clinical Reason for Override" (12%) and "Not Patient's Primary Team" (11%). Twenty-five entries (2%) were deemed to be angry or inappropriate. Examples included "Stop sending me delirium assessment", "this is irrelevant, restrict this message to intern log-ins" and "I am consultant and I have to prioritise". Conclusion: Bypass of cognitive screening alerts within the EPR by doctors is common. Qualitative analysis of reasons for bypassing electronic alerts may provide insights on physicians' perceptions to computer-generated prompts as well as informing future customisation and optimisation of alerts. Education and awareness amongst physicians regarding the nature and quality of documentation within electronic records is required.